Natural vibration frequencies of delaminated composite beams - Krawczuk, Marek; Ostachowicz, Wiesław; Żak, Arkadiusz (Computer Assisted Methods in Engineering and Science, 1996)
In the presented work a model of a layered, delaminated composite beam based on the finite elements method was introduced. In this model the beam was divided into finite elements, while the delamination was modelled using additional boundary conditions. One delaminated region in the cross-section of the beam was considered which extended to the full width of the beam. It was also assumed that the delamination was open. The influence of the delamination length and position on the changes of natural frequencies of flexural vibrations of the laminated composite cantilever beam were investigated.